Gender Performativity and Conceptual Metaphors in the Presidential Campaign Discourse: A case study from Georgia - Guliashvili, Nino (European Scientific Journal, ESJ, 2021)
Gender Performativity defines politicians’ verbal repertoire in accordance with the social context and expectations. Social actors construct their identities in the discourse through the work of words. Conceptual metaphors are supposed to be the cognitive models of linguistic metaphoric expressions manifested in the political discourse which tend to play a significant role in the social construction of gender. The present study focuses on the use of metaphors in two presidential candidates’ (Salome Zurabishvili and Grigol Vashadze) English interviews made during 2018 presidential election campaign in Georgia. Conceptual Metaphors: Politics is Journey, Politics is Sport and Politics is War are investigated in Salome Zurabishvili’s and Grigol Vashadze’s political speeches. The metaphoric choices the politicians make are socially determined and later on ascribed to their gender which may not be as binary as it is traditionally perceived. In today’s competitive world of politics women tend to manifest their agency through the language which is rendered masculine. Therefore, critical discourse analysis (CDA) is applied to investigate the discursive construction of gender and agency through conceptual metaphors.